'Great is Darwin and Bergson his poet': Julian Huxley's other evolutionary synthesis. Issue 1 (2nd January 2018) - Herring, Emily
SUMMARY: In 1912, Julian Huxley published his first book The Individual in the Animal Kingdom which he dedicated to the then world-famous French philosopher Henri Bergson. Historians have generally adopted one of two attitudes towards Huxley's early encounter with Bergson. They either dismiss it entirely as unimportant or minimize it, deeming it a youthful indiscretion preceding Huxley's full conversion to Fisherian Darwinism. Close biographical study and archive materials demonstrate, however, that neither position is tenable. The study of the Bergsonian elements in play in Julian Huxley's early works fed into Huxley's first ideas about progress in evolution and even his celebrated theories of bird courtship. Furthermore, the view that Huxley rejected Bergson in his later years needs to be revised. Although Huxley ended up claiming that Bergson's theory of evolution had no explanatory power, he never repudiated the descriptive power of Bergson's controversial notion of the élan vital . Even into the Modern Synthesis period, Huxley represented his own synthesis as drawing decisively on Bergson's philosophy.